2021
DOI: 10.1021/acs.jnatprod.0c01327
|View full text |Cite
|
Sign up to set email alerts
|

Marine Bile Natural Products as Agonists of the TGR5 Receptor

Abstract: Agonism of the G protein-coupled bile acid receptor "Takeda G-protein receptor 5" (TGR5) aids in attenuating cholesterol accumulation due to atherosclerotic progression. Although mammalian bile compounds can activate TGR5, they are generally weak agonists, and more effective compounds need to be identified. In this study, two marine bile compounds (5β-scymnol and its sulfate) were compared with mammalian bile compounds deoxycholic acid (DCA) and ursodeoxycholic acid (UDCA) using an in vitro model of TGR5 agoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Consistent with our findings, the regulatory effect of TGR5 on PKA has been confirmed by literature (Hu et al, 2021;Jin et al, 2021). Interestingly, many documents showed that TGR5 is involved in the regulation of intracellular Ca 2+ levels (Maczewsky et al, 2019;Bensalem et al, 2020;Halkias et al, 2021). Our present research found that TGR5 can stabilize endothelial cell mitochondrial dynamics and protect endothelial cells from HG damage.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our findings, the regulatory effect of TGR5 on PKA has been confirmed by literature (Hu et al, 2021;Jin et al, 2021). Interestingly, many documents showed that TGR5 is involved in the regulation of intracellular Ca 2+ levels (Maczewsky et al, 2019;Bensalem et al, 2020;Halkias et al, 2021). Our present research found that TGR5 can stabilize endothelial cell mitochondrial dynamics and protect endothelial cells from HG damage.…”
Section: Discussionsupporting
confidence: 92%
“…The stronger neurotrophic effects of DCA relative to CDCA are consistent with our findings that TGR5 signaling appears to mediate neurite outgrowth. DCA is a known activator of TGR5 [ 50 , 51 ], as is CDCA [ 52 , 53 ], though DCA is a more potent agonist of TGR5 than CDCA, which is reversed, i.e., CDCA is greater than DCA, for FXR agonism [ 54 ]. Of relevance to ALS, TCDCA is able to bind to the TGR5 receptor and activate it [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The stronger neurotrophic effects of DCA relative to CDCA is consistent with our ndings that TGR5 signaling appears to mediate the neurite outgrowth. DCA is a known activator of TGR5 [41,42] as is CDCA [43,44], though DCA is a more potent agonist of TGR5 than CDCA, which is reversed, i.e., CDCA greater than DCA, for FXR agonism [45]. Of relevance to ALS, TCDCA is able to bind to the TGR5 receptor and activate it [46,47].…”
Section: Discussionmentioning
confidence: 99%